Kristologi Pembebasan: Kajian Teologis-Antropologi terhadap Kristologi Pembebasan dalam Kaitan Sistem Tana’ di Toraja - Abialtar, Abialtar; Lino’, Alfari; Tandirerung, Lidya K. (KAMASEAN: Jurnal Teologi Kristen, 2023)
This study aims to (1) describe the views of the Toraja people about the tana' system; (2) Analyzing the Christology of Liberation in correlation with the practice of the tana' system in Toraja and (3) Constructing a Christology of Liberation which brings a transformative function to the self-understanding of the Kaunan (servants) in church and social life. The method used is a qualitative method with an anthropological paradigm and an ethnographic approach through literature review and field research (interviews and observations). The results of this study found that the tana' system is understood as a social stratum or level in society that leads to duties and responsibilities that are accepted as a way of regulating social life. The Christology of liberation brings a transformative function to every land' that gives birth to love and justice. Love moves the nobility (the highest tana') to embrace and express concern for the people who are accepted as fellow creatures who are in the same image and similar to God as well as co-workers with God in the sphere of service. Likewise, love brings you to understand yourself as a creation that is in the same image and similar to God who has also been redeemed through Jesus Christ to feel worthy, embraced and loved.